Direct Observation of Charge Injection From CH3NH3PbI3−xClx to Organic Semiconductors Monitored With sub‐ps Transient Absorption Spectroscopy. Issue 3 (23rd October 2018) - Horn, Jonas; Minda, Iulia; Schwoerer, Heinrich; Schlettwein, Derck
Abstract : Thin films of the hybrid perovskite CH3 NH3 PbI3− x Cl x are prepared in contact to poly(3, 4‐ethylenedioxythiophene)polystyrene sulfonate (PEDOT:PSS) or phenyl‐C61 ‐butyric acid methyl ester (PCBM) as model interfaces relevant in inverted perovskite solar cells (IPSCs) which provide some significant advantages over the established mesoporous cell concepts. Pump–probe absorption spectroscopy with femtosecond resolution is used to analyze injection of photo‐generated charge carriers from the perovskite to the PEDOT:PSS and PCBM layers by directly monitoring characteristic spectroscopic signatures of charge carriers in these contact phases. Such signal is identified for holes injected into the PEDOT:PSS layer, which appeared within the resolution of the measurement setup (<200 fs) proving ultrafast hole injection. Changes in the transient signals characteristic for the perovskite layer as reflected in the time constants obtained by global analysis confirmed this observation. Ultrafast injection of electrons into PCBM is also found based on the decay of signals characteristic for the excited state of the perovskite as well as by newly arising signals assigned to injected electrons into PCBM. Efficient injection of charge carriers following excitation of the perovskite film to both organic electron and hole conductors is thereby directly shown. Abstract : By using pump–probe spectroscopy, the authors analyze in detail the ultrafast charge injection of photoexcited charge carriers from a thin layer of CH3 NH3 PbI3− x Cl x to the organic semiconducting layers PEDOT:PSS and PCBM. The authors identify spectral signatures caused by injected charge carriers in the organic semiconductors and, therefore, find direct evidence for their ultrafast injection in addition to established slower channels.